Dodging a Draft: Gary Becker's Lost Paper on Conscription - Michael Gibbs; Tim Perri (Institute of Labor Economics (IZA), 2021)
Gary Becker wrote what may be the first economic analysis of conscription. Less than a decade later, economists played a key role in an important public policy debate during the Vietnam War, which eventually led to abolishment of the military draft. Becker had connections to many of those economists who studied the economics of conscription, and his paper foreshadowed many of the ideas in that literature. Despite this, none cited his paper on conscription. We discuss this history and speculate on this puzzle.
Keywords: M5; 330; conscription; labor market public policy